ALAT PENGHITUNG BENIH IKAN LELE MENGGUNAKAN PENGOLAHAN CITRA (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Catfish hatchery cultivation business is currently very high. This can be seen from the number of people who open catfish hatcheries and places to eat catfish but are still constrained in the process of calculating the number of catfish seeds. The method of calculating at this time is still manual and volumetric. Of the two methods, it is still very dependent on the person who counts the catfish seeds. Therefore, a catfish seed counter was made automatically in order to shorten the time of calculating the catfish, using a webcam. After testing the design of the catfish seed counter, it was found that, from the average percentage of tool error in 5 experiments in each calculation of the number of catfish seeds with a maximum data of 200 catfish seeds measuring 5 mm - 10 mm long, the results obtained are the average tool error is 8.92%. The calculation process time using the tool is faster than manual calculations. The main error in the calculation is caused by the number of catfish fry that are piled up and the different sizes of the seeds so that the reading is not stable or accurate.